Evaluation of temperature variances found with integral reefer containers during shipment of Japanese plums (Prunus salicina Lindl.) at dual and single temperature - Kapp, Anine A. C. (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScAgric)--Stellenbosch University, 2008.